Biomechanical, physiological and anthropometric determinants of backstroke swimming performance: A systematic review - González-Ravé, J. M.; González-Mohino, F.; Hermosilla Perona, F.; Rodrigo-Carranza, V.; Yustres, I.; Pyne, D. B. (Sports Medicine - Open, 2025)
Background Backstroke swimming is one of the four competitive strokes contested at international swimming events, and the second-slowest stroke after breaststroke. Achieving success in competition depends on the intricate interplay of various factors, and for top-ranked athletes, subtle differences can be decisive in determining the race outcome. The aim of this study is to identify the main energetic, biomechanical, and physiological factors influencing elite backstroke swimming performance in 50, 100, and 200-m events.